Opportunistic grazing: An efficient tool for enhancing rangeland health - Louhaichi, Mounir; Gamoun, Mouldi (International Center for Agricultural Research in the Dry Areas, 2024)
This Innovation Brief explored the concept of opportunistic grazing as a sustainable tool to enhance rangeland health. Opportunistic grazing involved allowing livestock to graze on available forage during favorable conditions, effectively utilizing high-quality forage and improving ecosystem health. This approach promoted better livestock nutrition, enhanced rangeland biodiversity, and mitigated overgrazing by concentrating grazing pressure during periods of rapid plant growth. Key benefits included improved animal health, reduced soil compaction, and flexibility for pastoralists to adapt to variable climatic conditions. By mimicking natural herbivory, opportunistic grazing fostered a balanced distribution of grazing pressure and supported long-term rangeland productivity.